135k views
3 votes
Convert the equation, x - 2y = 6, into slope-intercept form.

User Zhon
by
4.9k points

1 Answer

2 votes

Answer:


\boxed {y = -(1)/(2)x + 3}

Explanation:

Convert the equation from Standard Form to Slope-Intercept Form:


Ax + By = C
y = mx + b

-The following equation:


x - 2y = 6

-Solve:


x - 2y = 6


x - x - 2y = 6 - x


2y = -x + 6


(2y)/(2) = (-x)/(2) + (6)/(2)


\boxed {y = -(1)/(2)x + 3}

So, the equation in Slope-Intercept Form is
y = -(1)/(2)x + 3.

User Apolka
by
5.0k points